2017
DOI: 10.1177/0308518x17700394
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic markets and community food security in an urban “food desert”

Abstract: In recent years, the concept of food desert has come to dominate research and policy debates around food environments and their impacts on health, with mounting evidence that low-income neighborhoods of color lack large supermarkets and therefore may have limited access to fresh, affordable, and healthy foods. We argue that this metaphor, which implies an absence of food, is misleading and potentially detrimental to the health of poor and racially diverse communities because it ignores the contribution of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…For instance, research shows that ethnic markets can have a positive impact in low-income urban neighborhoods [52]. Joassart-Marcelli, Rossiter, and Bosco, in their analysis of ethnic food markets in San Diego, find that ethnic markets can play a large role in providing residents with nutritious, affordable, and culturally acceptable food-thereby contributing to community food security.…”
Section: Implications Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, research shows that ethnic markets can have a positive impact in low-income urban neighborhoods [52]. Joassart-Marcelli, Rossiter, and Bosco, in their analysis of ethnic food markets in San Diego, find that ethnic markets can play a large role in providing residents with nutritious, affordable, and culturally acceptable food-thereby contributing to community food security.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Joassart-Marcelli, Rossiter, and Bosco, in their analysis of ethnic food markets in San Diego, find that ethnic markets can play a large role in providing residents with nutritious, affordable, and culturally acceptable food-thereby contributing to community food security. Provided the unwillingness of supermarkets and supercenters to locate to poor urban areas and the need for nutritious, affordable food, they argue that it may be more efficient and equitable for government programs to financially assist ethnic markets and smaller locally-owned grocery stores to increase the distribution and marketing of healthy foods rather than to spend resources trying to entice a large supermarket to locate to underserved areas [52]. Given the recent failure of the city of Dallas to partner with a large supermarket to open a branch in south Dallas, we agree with this sentiment.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Health benefits of shopping for food at ethnic markets are not extensively explored. Ethnic markets in low‐income community provides residents with culturally acceptable and nutritionally adequate nonemergency foods, thus contribute to food security (Joassart‐Marcelli et al, ). Our own study in the nearby City of Schenectady demonstrated that shopping for food often or sometimes at ethnic markets was significantly and independently associated with lower BMI among Guyanese immigrant residents (Hosler et al, ).…”
Section: Discussion: Ethnic Marketsmentioning
confidence: 99%
“…Most food environment studies do not incorporate cultural variations in food selections in their assessments (Odoms-Young et al, 2009), despite that cultural acceptability is an important dimension of the food environment (Short, Guthman, & Raskin, 2007). Furthermore, ethnic market is often erroneously perceived as dirty places associated with unhealthy, pricy foods, a view that stems from the societal division along the lines of race and class (Joassart-Marcelli, Rossiter, & Bosco, 2017). However, similar to our findings, existing studies have revealed that ethnic markets were more likely to have wider selections of healthy foods at lower prices than nonethnic stores (Joassart-Marcelli et al, 2017), and they thrive as a niche business in ethnically diverse low-income neighborhoods (Short et al, 2007).…”
Section: Discussion: Ethnic Marketsmentioning
confidence: 99%
See 1 more Smart Citation